Safety and efficacy of immune checkpoint inhibitors in advanced urological cancers with pre-existing autoimmune disorders: a retrospective international multicenter study. Issue 1 (26th March 2020) - Martinez Chanza, Nieves; Xie, Wanling; Issa, Majd; Dzimitrowicz, Hannah; Tripathi, Abhishek; Beuselinck, Benoit; Lam, Elaine; Zakharia, Yousef; Mckay, Rana; Shah, Sumit; Mortazavi, Amir; R. Harrison, Michael; et al.
Abstract : Background: There is limited experience regarding the safety and efficacy of checkpoint inhibitors (CPI) in patients with autoimmune disorders (AD) and advanced urological cancers as they are generally excluded from clinical trials due to risk of exacerbations. Methods: This multicenter retrospective cohort analysis of patients with advanced renal cell cancer (RCC) and urothelial cancer (UC) with pre-existing AD treated with CPI catalogued the incidence of AD exacerbations, new immune-related adverse events (irAEs) and clinical outcomes. Competing risk models estimated cumulative incidences of exacerbations and new irAEs at 3 and 6 months. Results: Of 106 patients with AD (58 RCC, 48 UC) from 10 centers, 35 (33%) had grade 1/2 clinically active AD of whom 10 (9%) required corticosteroids or immunomodulators at baseline. Exacerbations of pre-existing AD occurred in 38 (36%) patients with 17 (45%) requiring corticosteroids and 6 (16%) discontinuing CPI. New onset irAEs occurred in 40 (38%) patients with 22 (55%) requiring corticosteroids and 8 (20%) discontinuing CPI. Grade 3/4 events occurred in 6 (16%) of exacerbations and 13 (33%) of new irAEs. No treatment-related deaths occurred. Median follow-up was 15 months. For RCC, objective response rate (ORR) was 31% (95% CI 20% to 45%), median time to treatment failure (TTF) was 7 months (95% CI 4 to 10) and 12-month overall survival (OS) was 78% (95% CI 63% to 87%). For UC, ORR was 40% (95% CI 26% to 55%), median TTF was 5.0 months (95% CI 2.3 to 9.0) and 12-month OS was 63% (95% CI 47% to 76%). Conclusions: Patients with RCC and UC with well-controlled AD can benefit from CPI with manageable toxicities that are consistent with what is expected of a non-AD population. Prospective study is warranted to comprehensively evaluate the benefits and safety of CPI in patients with AD.